Analisis Framing Pemberitaan Pada Isu Pemecatan Karyawan CNN Indonesia di Tempo.com. (Analisis Framing Model Robert N. Entman) - Nasrullah, Mochammad (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2025)
The Mass media are one of the fourth pillars of democracy guaranteed by the 1945 Constitution. In it, a journalist plays an important role in digging up information to be conveyed to the public. But unfortunately, the rights and obligations for journalists are not given properly, and the termination of employment as experienced by CNN Indonesia journalists. This study aims to analyze the news of the dismissal of CNN Indonesia employees in the Tempo.co media using Robert N. Entman's framing analysis as an analytical tool, with four stages, namely: define problem, diagnose causes, make moral judgment, and treatment recommendation. The results of the study show that Tempo.co framed the news of the issue of the dismissal of CNN Indonesia employees as a result of the termination of employment by CNN Indonesia management due to the formation of a labor union, namely the CNN Indonesia Workers Union or SPCI. Tempo journalists saw that the actions taken by CNN Indonesia management were not by the 1945 Constitution and Law Number 21 of 2000 concerning Labor Unions. Many parties regretted the termination of the employment of CNN Indonesia employees because it was not by the freedom of expression guaranteed by law.